Tetrahedral and polyhedral mesh evaluation for cerebral hemodynamic simulation–a comparison - Spiegel, Martin; Redel, Thomas; Zhang, Yao; Struffert, Tobias; Hornegger, Joachim; Grossman, Robert G.; Dörfler, Arnd; Karmonik, Christof (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2009)
Computational fluid dynamic (CFD) based on patient-specific medical imaging data has found widespread use for visualizing and quantifying hemodynamics in cerebrovascular disease such as cerebral aneurysms or stenotic vessels. This paper focuses on optimizing mesh parameters for CFD simulation of cerebral aneurysms. Valid blood flow simulations strongly depend on the mesh quality. Meshes with a coarse spatial resolution may lead to an inaccurate flow pattern. Meshes with a large number of elements will result in unnecessarily high computation time which is undesirable should CFD be used for planning in the interventional setting. Most CFD simulations reported for these vascular pathologies have used tetrahedral meshes. We illustrate the use of polyhedral volume elements in comparison to tetrahedral meshing on two different geometries, a sidewall aneurysm of the internal carotid artery and a basilar bifurcation aneurysm. The spatial mesh resolution ranges between 5,119 and 228,118 volume elements. The evaluation of the different meshes was based on the wall shear stress previously identified as a one possible parameter for assessing aneurysm growth. Polyhedral meshes showed better accuracy, lower memory demand, shorter computational speed and faster convergence behavior (on average 369 iterations less).
UnivIS-Import:2017-01-09:Pub.2009.tech.IMMD.IMMD5.tetrah_3